A STUDY ON THE AWARENESS, PREFERENCE AND SATISFACTION OF POLICY HOLDERS TOWARDS LIC WITH SPECIAL REFERENCE TO MALAPPURAM DISTRICT - Jayapriya; Chandni, P.S. (International Journal of Research -GRANTHAALAYAH, 2016)
Life insurance is actually an agreement between the insured and the insurer in which the policy holder accepts to pay regular premium to the insurer. In return, the insurer guarantees monetary protection to the insured in case of any accident or mishaps. If the insured dies in accident, financial help is provided to his family members. Thus, life insurance is necessary as it provides protection to not only for the insured but also to the family of insured in case of any unwanted disaster. A thriving insurance sector is very important to every modern economy. Firstly because it encourages the habit of saving, secondly because it provides safety to rural and urban enterprises and productive individuals. At present the number of customers investing in LIC is increasing rapidly due to various reasons. Some of them are investing to get tax advantage, while some others are for children education,children marriage, pension for future etc.The number of LIC agents are also increasing .They are providing adequate services to their customers. This study helps to find out the awareness level of customers towards various schemes of LIC and to measure the preference and satisfaction of policy holders towards LIC. The data required for the study are collected from 100 customers of LIC from Malappuram district through well designed questionnaire. Simple percentage and chi square test are used for analyzing the collected data.